PENGARUH PENGGUNAAN SARI BUAH STRAWBERRY TERHADAP PENAMPILAN, TEKSTUR, AROMA, WARNA DAN RASA SEBAGAI PENGGANTI AIR MINERAL DALAM PEMBUATAN CHURROS - Artin Bayu Mukti; Angela Devi Widayanti1; Ndaru Prasastono (Jurnal Pariwisata Indonesia, 2021)
Desserts usually have a sweet and refreshing taste, sometimes some are salty or a combination thereof. Churros are an example of a dessert. Churros are Spanish and Portuguese pastries. Churros are cooked by frying. This research was conducted to determine the effect of using strawberry juice on the appearance, texture, aroma, color and taste as a substitute for mineral water in making Churros. The method used in this research is descriptive type, while the data collection technique is in the form of organoleptic test assessment. Data analysis and discussion used in this study is quantitative data analysis, with a total of 120 respondents. While the conclusion of this research is the effect of using strawberry juice on the appearance, texture, aroma, color and taste as a substitute for mineral water in making Churros.